2019
DOI: 10.3892/or.2019.7251
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑126‑3p inhibits the proliferation, migration, invasion, and angiogenesis of triple‑negative breast cancer cells by targeting RGS3

Abstract: Triple-negative breast cancer (TNBC) is characterized by fast progression with high potential for metastasis, and poor prognosis. The dysregulation of microRNAs (miRNAs) occurring in the initiation or progression of cancers often leads to aberrant gene expression. The aim of the present study was to explore the function of miR-126 in TNBC cells. Expression levels of miR-126-3p were determined by quantitative real-time PCR. Then, the effects of miR-126-3p on migration, proliferation, invasion, and angiogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…36 More importantly, miR-140-3p, functioning as a tumor suppressor, prevents the progression of lung cancer by targeting ATP6AP2. 37 Apart from that, hsa-miR-140-3p exhibits tumor-suppressive effects on breast cancer proliferation and migration. 38 Similar to its role in lung cancer, our study showed that miR-140-3p inhibits GRN gene and downregulates the MAPK signaling pathway, thereby inhibiting EMT and invasion and metastasis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…36 More importantly, miR-140-3p, functioning as a tumor suppressor, prevents the progression of lung cancer by targeting ATP6AP2. 37 Apart from that, hsa-miR-140-3p exhibits tumor-suppressive effects on breast cancer proliferation and migration. 38 Similar to its role in lung cancer, our study showed that miR-140-3p inhibits GRN gene and downregulates the MAPK signaling pathway, thereby inhibiting EMT and invasion and metastasis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs can regulate their targets to exert their biological effects ( 19 , 20 ). For example, in glioma, miR-320a inhibits cell invasion and migration by targeting aquaporin 4 ( 21 ), and in liver cancer, miR-498 inhibits cell proliferation and metastasis by targeting zinc finger E-box binding homeobox 2 ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, LRP6 expression was found to be upregulated, which was consistent with other studies reporting that LRP6 expression was also increased in different tumor types, such as human triple negative breast cancer ( 31 ) and prostate cancer ( 33 ). It is well known that miRNAs may exert their biological roles via the regulation of their target mRNAs ( 19 22 ). Therefore, the current study investigated the association between miR-590 and LRP6 by analyzing their expression in 28 pairs of ESCC tissues, and subsequently identified a weak negative correlation between the two factors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the miR-181a was involved in TNBC metastasis via elevated expression of Bim [72]. [115,116] miR-373 TXNIP Induces cancer cell EMT and metastasis [117,118] miR-10b HOXD10 Promotes invasion and metastasis [119] miR-21 PTEN Lymph node metastasis [120] miR-17/92 cluster COL4A3, LAMA3, TIMP2/3 Lymph node metastases, promote metastasis [121,122] miR-629-3p LIFR Lung metastases [123] miR-455-3p EI24 Promotes proliferation, invasion, and migration [124] miR-125b APC Promotes proliferation, metastasis, and EMT [125] miR-181a Bim Promotes EMT, migratory, and invasive [72] Oncosuppressor miRNAs miR-200a/b/c PKCα, UBASH3B, XIAP Suppress proliferation, migration, invasion, and metastasis, promote apoptosis [77,126,127] miR-205 Unknown Lymph node metastasis [128] let-7 RAS, c-Myc Block growth and reduce metastasis [129] miR-145 MUC1, Arf6, JAM-A, Fascin Reduce cell motility, invasiveness, and metastasis [130][131][132] miR-206 CORO1C Regulates metastasis [133] miR-30a ROR1 Associates with high histological grade and more lymph node metastasis [134] miR-190a/940 Unknown Prevents metastasis and cell invasion [19,135] miR-33b HMGA2, SALL4, Twist1 Inhibit metastasis [114] miR-146a-5p SOX5 Inhibits proliferation and metastasis [136] miR-150 HMGA2 Inhibits metastasis [137] miR-124 ZEB2 Inhibits invasion and metastasis [138] miR-148a WNT1, NRP1 Suppress metastasis [139] miR-126-3p RGS3 Inhibits proliferation, migration, invasion, and angiogenesis [140] miR-508-3p ZEB1 Inhibits cell invasion and EMT [141] miR-613 Daam1 Inhibits cell migration and invasion [142] miR-519d-3p LIMK1 Suppresses growth and mot...…”
Section: Mirnas In Regulation Of Metastasis In Tnbcmentioning
confidence: 99%
“…MiR-190a and miR-940 were also significantly reduced in TNBC tissues to prevent metastasis and cell invasion [19,135]. Additionally, several miRNAs function as oncosuppressor miRNAs involved in metastasis of TNBC, such as miR-33b [114], miR-146a-5p [136], miR-150 [137], miR-124 [138] and miR-148a [139], miR-126-3p [140], miR-508-3p [141], miR-613 [142], miR-519d-3p [143], miR-26a [144], and miR-130a [145], by targeting HMGA2, SALL4 and Twist1, SRY-box transcription factor 5 (SOX5), HMGA2, ZEB2, wnt family member 1 (WNT1) and neuropilin 1 (NRP1), the regulator of G-protein signaling 3 (RGS3), ZEB1, disheveled-associated activator of morphogenesis 1 (Daam1), LIM domain kinase 1 (LIMK1), metadherin (MTDH), FOSL1, and zonula occludens 1 (ZO-1, also called TJP1), respectively.…”
Section: Mirnas In Regulation Of Metastasis In Tnbcmentioning
confidence: 99%